Sex-specific differences and postoperative outcomes of minimally invasive and sternotomy valve surgery - Moscarelli, Marco; Lorusso, Roberto; Angelini, Gianni D; Di Bari, Nicola; Paparella, Domenico; Fattouch, Khalil; Albertini, Alberto; Nasso, Giuseppe; Fiorentino, Francesca; Speziale, Giuseppe (European Journal of Cardio-Thoracic Surgery, 2022)
Abstract